Conclusions of the Central American Seminar on IFLA-UNESCO Manifestos for Public Libraries, Schools and the Internet - Miranda Arguedas, Alice (2007)
Some considerations are presented on the Central American Seminar held in 2007, takes into consideration the fundamental objectives that guided this event, also mentions the current state of public libraries, school libraries and the use of the Internet in the Central American region. Finally, reference is made to the workshops and the different discussion spaces that were established based on the manifesto, as well as the guidelines and directives that guide library development.